Heat transfer, exergy, and cost: A sustainable analysis of concentric tube heat exchangers - Samer Ali; Chadi Nohra; Georges El Achkar; Jalal Faraj; Mahmoud Khaled (Case Studies in Thermal Engineering)
This study investigates the heat transfer, exergetic performance, and overall cost of counter-flow concentric tube heat exchangers under various geometric and flow conditions. A systematic parametric analysis is performed using 2700 two-dimensional axisymmetric computational fluid dynamics simulations. The analysis spans Reynolds numbers from 1000 to 20000, covering both laminar and turbulent regimes, and considers four fluid combinations (air–air, air–water, water–air, water–water) with temperature-dependent properties. Geometric variations include three inner diameters (0.01 m, 0.02 m, 0.05 m), three diameter ratios (1.25, 1.5, 3), and three lengths (0.4 m, 0.6 m, 4 m). Results show that increasing Reynolds number enhances the heat transfer rate and overall heat transfer coefficient. For instance, the heat transfer coefficient remains below 60 W/m2⋅K for air–air configurations, rises to 100–150 W/m2⋅K for air–water and water–air cases, and reaches up to 2000 W/m2⋅K for water–water setups. Smaller inner diameters, lower diameter ratios, and longer heat exchangers achieve high effectiveness and exergetic efficiencies up to 0.8, indicating superior thermodynamic performance. However, these configurations often incur higher operating costs, exceeding 10,000–12,000 USD over a 10-year period for long, small-diameter units, compared to 2,000–2,600 USD for shorter or larger-diameter designs. This research provides a comprehensive framework to balance heat transfer enhancement, exergy utilization, and cost-effectiveness in designing sustainable heat exchanger systems.